Validação do subconjunto terminológico cipe® para pacientes com dor oncológica - Carvalho , Marisaulina Wanderley Abrantes de (2017)
Introduction: Terminology Subset of ICNP® for patients with cancer pain, is configured as a technology of care, constituting then as a tool in providing a systematic nursing care for patients with cancer pain, considering that the pain It is characterized as the main factor of suffering related to cancer and presents multidimensional and subjective characteristics, thus making it difficult to review. Objective: To perform the validation, content and clinical, the terminological Subset ICNP® for patients with cancer pain, in the light of the cancer pain model and the theory of comfort. Method: Research methodology kind held in two stages in which appropriate techniques were used to obtain the results and the achievement of objectives: 1) content validation of the concepts of diagnosis / constant results in terminological Subset of ICNP® for patients with cancer pain and 2) clinical validation of that subset, by carrying out clinical case studies. Results: We developed operational definitions for 68 nursing diagnoses subset evaluated by experts, and all considered validated by obtaining a higher IC 80%. 68 concepts of validated diagnostic and their nursing interventions distributed aspect/comfort of cancer pain were validated by experts getting to the appearance/physical comfort 23 (82.15%) of nursing diagnosis and 77 (78.6%) validated nursing interventions; for aspect/psychological comfort of cancer pain 19 (65.5%) nursing diagnosis and 38 (64.4%) interventions were considered validated; and the appearance/comfort sociocultural and spiritual cancer pain 6 (54.5%) nursing diagnoses e 10 (40.0%) interventions were validated. From these results the terminological subset ICNP® for patients with cancer pain was structured including presentation, significance for nursing, theoretical model, and concepts nursing diagnoses/outcomes and interventions. Clinical validation was performed on five patients, characterized as follows: an infected in clinical treatment, one in radiotherapy treatment, one in chemotherapy/radiotherapy, one in surgery/chemotherapy and a terminal. Conclusion: It is believed that the validation the terminology subset of ICNP® for patients with cancer pain and in practice the use of the concepts the nursing diagnoses/outcomes and interventions contained provides means for nurses who work in this area, can provide patients with quality care.